Awareness of cervical cancer risk factors and utilisation of pap-smear testing among health workers in Ibadan, Nigeria (2017)
Cervical cancer is a major reproductive health problem among women in Nigeria, every woman who has ever been sexually active is at risk. Certain factors also increase the risk of developing the disease. Cervical cancer can usually be found early by having regular Pap smear tests but this test is rarely provided and hardly utilised by women. This study was aimed at finding out the level of awareness of female health workers and the level of utilization of pap smear testing. The study was carried out using descriptive survey research design and the total population of 623 health workers in government owned hospitals were used as respondents for the study. Only 502 of the structured questionnaire were returned. Reliability of the instrument was determined using a test-retest method with Pearson Product Moment correlation and it yielded reliability co-efficient of 0.73. Data collected was analysed using descriptive statistics of frequency count and percentage for the research question, while inferential statistics of chi-square and regression were used to determine the level and the direction of relationship between the independent and the dependent. The level of significance was set at p-value <0.05. The results shows that only 118 (23.5%) have had pap smear test while 384 (76.5%) have not. Also, awareness of cervical cancer risk factors was significant (X2cal 33.426, X2crit =11.071, df= 5, p< 0.05) among health workers. But, this awareness of the risk factors did not significantly influence (13 =.084, t= 1.069, p> 0.05) the utilization of pap-smear testing among female health workers in Ibadan. It is surprising to note that the awareness of cervical cancer risk factors did not influence the utilization of pap- smear testing among health workers in Ibadan. In recommendation, female health workers should be sensitised and encouraged to subject themselves to pap-smear testing as the experience will serve as a source of empowerment in their pivotal role of adviser and developing consciousness, reliance and cooperation of other women.